Primary humanities learning through enquiry - Pickford, Tony; Garner, Wendy; Jackson, Elaine 1954- (Sage, 2013)
Providing a broad and balanced overview of the teaching of primary history and primary geography Primary Humanities: Learning Through Enquiry is indispensable reading for all primary teacher education students wishing to develop their understanding of teaching humanities subjects.